UNIT 6.37 High‐Sensitivity Detection of PNH Red Blood Cells, Red Cell Precursors, and White Blood Cells. Issue 1 (1st April 2015) - Sutherland, D. Robert; Illingworth, Andrea; Keeney, Michael; Richards, Stephen J.
Abstract : Flow cytometry is the method of choice to 'diagnose' paroxysmal nocturnal hemoglobinuria (PNH) and has led to improved patient management. Most laboratories have limited experience with PNH testing, and many different flow approaches are used. Careful selection and validation of antibody conjugates has allowed the development of reagent cocktails suitable for detection of PNH RBCs, CD71+ reticulocytes, and WBCs in clinical/sub‐clinical PNH samples. A CD235a‐FITC/CD59‐PE assay was developed capable of detecting Type III PNH RBCs at 0.01% sensitivity. A protocol targeting immature CD71+ RBCs can detect PNH reticulocytes at similar sensitivity. Four‐color FLAER‐based neutrophil and monocyte assays were developed to detect PNH phenotypes at a level of 0.01% and 0.04% sensitivity, respectively. For instrumentation with five or more PMTs, a single‐tube 5‐color FLAER/CD157‐based assay to simultaneously detect PNH neutrophils and monocytes is described. Using these standardized approaches, results have demonstrated good intra‐ and inter‐laboratory performance characteristics even in laboratories with little prior experience performing PNH testing. © 2015 by John Wiley & Sons, Inc.